Melatonin enhances drought tolerance by affecting jasmonic acid and lignin biosynthesis in wheat (Triticum aestivum L.) - Luo, Mingzhao (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.